The Use of Video as an Authentic Materials in Improving Students’ Writing Skills of Recount Text - Dita Anisa Pratiwi; Dedeh Rohayati (Journal of English Education Program (JEEP), 2023)
This research was purposed to measure the significant difference on the use of video as an authentic material to improve students’ writing skills and investigate the use of video as authentic material in students’ writing skills on recount text. The present study applied cluster random sampling technique that implemented a mixed-method with the type of true-experimental design. A series of pretest-posttest for the quantitative data and interview for the qualitative data were utilized. The sample of the present study employed 30 students as the experimental and control group. The documentation of students’ tests was used to extract the data. The result showed that there was significant difference in students’ writing skills before and after being taught by means of video as an authentic material.  Meanwhile, the interview showed that students with high, middle and low achiever gave positive responses about using video as an authentic material in improving writing recount text. The study concluded that the use of video as an authentic material has contributed a good impact to students’ writing recount text with high, middle and low achiever, although it did not give significant impact in students’ learning outcomes particularly in writing recount text.